Increased prevalence and new evidence of multi-species chelonid herpesvirus 5 (ChHV5) infection in the sea turtles of Mabul Island, Borneo - Dexter Miller Robben; Pushpa Palaniappan; Aswini Leela Loganathan; Vijay Kumar Subbiah (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Fibropapillomatosis (FP) is a debilitating tumor disease affecting all species of sea turtles globally. The most probable etiological agent for FP is the chelonid herpesvirus 5 (ChHV5). A 2015–2016 field survey of the sea turtles at Mabul Island, Sabah, Malaysia, found three green turtles (Chelonia mydas) with FP tumors. However, the presence of ChHV5 was confirmed in 7.8% (9/115) green turtles and was absent (0/16) in the hawksbill (Eretmochelys imbricata) turtles, as determined through molecular approaches. Subsequent to this, we managed to conduct field sampling of sea turtles in November 2019, just prior to the pandemic lockdown. Here, we aim to determine the extent of ChHV5 infection, and whether the virus has spread to other species of sea turtles around Mabul Island after the first reports of ChHV5 and FP. A total of 69 tissue samples were obtained from green (63), hawksbill (5), and olive ridley (Lepidochelys olivacea) (1) turtles in November 2019. We observed only one green turtle that exhibited FP tumors. To determine the presence of ChHV5, viral DNA was isolated from all the tissue samples, and polymerase chain reaction (PCR) analysis targeting three highly conserved regions of the virus, i.e., the capsid protein gene, glycoprotein H gene, and glycoprotein B gene, was performed. Out of 63 green turtles, 27 were positive for the presence of the virus. The prevalence of ChHV5 in the green turtles showed an increase of 42.9% as compared to the previous sampling conducted in 2015–2016. Additionally, for the first time, three out of the five hawksbill turtles, and one olive ridley turtle, were also PCR-positive for the virus. In conclusion, this study reveals that there has been an increase in ChHV5 infection among turtles in Mabul Island over the last 3 years. ChHV5 should be considered a potential threat, and mitigation efforts should be taken to prevent the spread of infection among the endangered sea turtles of Mabul Island and surrounding islands within the Coral Triangle.